Can P-glycoprotein influence the bioavailability of iminosugar-based glucosylceramide synthase inhibitors? - Norris-Cervetto, E; Butters, T; Martin, C; Modok, S; Dwek, R; Callaghan, R (2006)
Recently developed glucosylceramide synthase inhibitors with enhanced hydrophobicity display increased bioavailability in the central nervous system (CNS). Have these improvements come at a potential risk given that the improved glucosylceramide synthase inhibitors bear the hallmarks of P-glycoprotein substrates? This question warrants attention given the potential to induce adverse drug interactions or toxicity, if glucosylceramide synthase inhibitors are administered with other P-glycoprotein substrates. The aim of this study was to determine if glucosylceramide synthase inhibitors are substrates for the multidrug transporter P-glycoprotein. Direct measurements of glucosylceramide synthase inhibitors binding to P-glycoprotein were examined, as was their ability to modulate transport by the protein. The more hydrophobic glucosylceramide synthase inhibitors caused a reduction in drug binding to P-glycoprotein. However, the compounds did not achieve this by direct interaction with the protein, but through a general membrane perturbation. Furthermore, the alterations in drug-P-glycoprotein interaction did not manifest as altered cellular accumulation of glucosylceramide synthase inhibitors or altered efficacy to reduce cellular glycolipid levels. Consequently, P-glycoprotein expression will not contribute significantly to the pharmacokinetic profile of the iminosugar glucosylceramide synthase inhibitors.